2016
DOI: 10.1002/adhm.201500872
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Contrast‐Agent‐Loaded Fibers for Colon‐Targeted MRI

Abstract: Magnetic resonance imaging (MRI) is a diagnostic tool used for detecting abnormal organs and tissues, often using Gd(III) complexes as contrast-enhancing agents. In this work, coreshell polymer fibers have been prepared using coaxial electrospinning, with the intent of delivering Gd(DTPA) (gadolinium (III) diethylenetriaminepentaacetate hydrate) selectively to the colon. The fibers comprise a poly(ethylene oxide) (PEO) core loaded with Gd(DTPA), and a Eudragit S100 shell. They are homogeneous, with distinct co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 55 publications
3
54
1
Order By: Relevance
“…These nanofiber mats have both large surface area , 3D web structures with huge porosity [16,17]. For the cylindrical nanofibers, their volume (V) can be roughly calculated according to the following concept.…”
Section: A Calculation About the Surface Enlargement From 1d Nanofibersmentioning
confidence: 99%
“…These nanofiber mats have both large surface area , 3D web structures with huge porosity [16,17]. For the cylindrical nanofibers, their volume (V) can be roughly calculated according to the following concept.…”
Section: A Calculation About the Surface Enlargement From 1d Nanofibersmentioning
confidence: 99%
“…29 In comparison with the relaxivities of fibers loaded with Gd(DTPA) only (Tables S2 and S3), those of Gd(DTPA)/indomethacin fibers were found to be somewhat lower (e.g. F3 has r 1 =10.13 s -1 mM -1 and r 2 =14.69 s -1 mM -1 , while the indomethacin-free analogue F3' has r 1 =12.29 s -1 mM -1 and r 2 =18.68 s -1 mM -1 ).…”
Section: Proton Relaxivitiesmentioning
confidence: 99%
“…29 Gd(DTPA) was found to retain its ability to act as contrast agent after electrospinning. It was also demonstrated that functional ingredients embedded in the core of the fibers can be effectively transferred to the colonic mucosa, permitting the latter to be imaged.…”
Section: Introductionmentioning
confidence: 99%
“…But this concept has a very close relationship with a series of instrumental analyses [20][21]. Good compatibility is prerequisite for the designed materials, for their storage or reactions, so that the vessel and other apparatus will not be damaged by its contents.…”
Section: High Correlation Between the "Compatibility" And The Inmentioning
confidence: 99%